INDUKSI KETAHANAN DAN PERTUMBUHAN BIBIT KELAPA SAWIT DENGAN BAHAN PENGINDUKSI BERBEDA JAMUR Trichoderma virens ENDOFIT TERHADAP PENYAKIT BUSUK BATANG ATAS - Halimah, Nur; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The Diseases found in oil palm plantations is the Upper Stem Rot (BBA) caused by pathogens Ganoderma sp. The alternatives that can used in controlling the disease BBA is by use endophyte microorganisms derived from plant tissue one of the Trichoderma virens endophyte. This study aimed to determine the effect of the administration of the different material inducer T. virens endophyte and get the best inducers ingredient in promoting growth and controlling upper stem rot disease on the oil palm seedlings, This research has been conducted in the experimental garden of the Faculty of Agriculture, State University of Riau, Industrial Business Unit Biofertilizer and Biopesticides University of Riau, Laboratory of Soil Science, Faculty of Agriculture, University of Riau, the Laboratory photomicrography and Laboratory of Biochemistry, Faculty of Mathematics and Natural Sciences, University of Riau, on Campus Binawidya km 12.5 Baru Simpang Village District of Handsome Pekanbaru. This study was conducted in May 2016 to November 2016. This study was conducted experiments using completely randomized design with 3 treatments and 7 replications so that obtained 21 experimental units. Data were analyzed statistically by ANOVA and tested with LSD at 5% level. The results showed that treatment of inducing materials in the form of T. virens endophyte suspension showed is the best treatment to be better increase plant height, stem diameter, root volume, and tend to be higher in prolong the incubation period, reduce the intensity of the disease, and increases the concentration of salicylic acid in the leaves of oil palm seedlings. Keywords: Upper Stem Rot, Trichoderma virens endophyte, The Induction of Resistance